2011
DOI: 10.1099/jmm.0.031815-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary infections due to non-capsulated Haemophilus influenzae

Abstract: We present two cases of non-capsulated Haemophilus influenzae hepatobiliary infection and review the literature. Such cases are rare, and prior to routine immunization against H. influenzae serotype b invasive Haemophilus disease was largely caused by capsulated strains. The epidemiology of invasive Haemophilus infections has changed and the number of cases of intra-abdominal and hepatobiliary infection may be underestimated due to current microbiological processing practices. Case reports Case 1A 52-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Our results indicate that Hie and Hif share many features characteristic of invasive ncHi disease, such as patient age distribution, higher risk for infection among vulnerable populations, and higher CFR compared with Hib ( 7 ). Certain features that were previously attributed primarily to ncHi, such as causing hepatobiliary disease ( 28 , 29 ) and disease during pregnancy ( 30 ), were also observed among Hie and Hif case-patients, respectively, in our study. The proportion of case-patients with comorbidities in our cohort was similar to previous smaller studies (60%–80%) ( 13 , 27 , 31 34 ) and to that among ncHi case-patients ( 13 , 26 , 33 , 35 37 ).…”
Section: Discussionsupporting
confidence: 74%
“…Our results indicate that Hie and Hif share many features characteristic of invasive ncHi disease, such as patient age distribution, higher risk for infection among vulnerable populations, and higher CFR compared with Hib ( 7 ). Certain features that were previously attributed primarily to ncHi, such as causing hepatobiliary disease ( 28 , 29 ) and disease during pregnancy ( 30 ), were also observed among Hie and Hif case-patients, respectively, in our study. The proportion of case-patients with comorbidities in our cohort was similar to previous smaller studies (60%–80%) ( 13 , 27 , 31 34 ) and to that among ncHi case-patients ( 13 , 26 , 33 , 35 37 ).…”
Section: Discussionsupporting
confidence: 74%
“…Overall, pneumonia is the most frequent presentation, with invasive NTHi disease and NTHi pneumonia incidence increasing with age, particularly in older adults with underlying respiratory tract comorbidities, such as COPD and emphysema (204,208). Other clinical presentations, such as epiglottitis (once a characteristic of invasive Hib disease) and skeletal and soft tissue infections, are uncommon, but cholecystitis (209) and urolithiasis (210) appear to be a particular feature of invasive NTHi infection in adults. The morbidity rate of invasive NTHi infections is high in older adults.…”
Section: Nthi Infections In Older Adultsmentioning
confidence: 99%
“…The aforementioned Swedish study, for example, reported that 48% of 101 invasive NTHi cases had severe sepsis or septic shock and 20% required intensive care. 120 Reported case fatality ratio (CFR) for invasive NTHi disease range between 12-22%, 122,125,155,157,158,160 and is associated with age, clinical presentation, presence of co-morbidity and duration of follow-up after infection. In Europe, compared with Hib, the age-adjusted odds ratio for death from invasive NTHi disease was 2•4 (95% CI, 1•9-3•1, P < 0•0001) overall, 3•3 (95% CI, 1•5-7•5; P = 0•004) for pneumonia and 3•3 (95% CI, 1•5-7•5; P = 0•004) for bacteraemia, with no significant difference observed for meningitis.…”
Section: Highlighting the Need For Further Research On Perinatal Nthi Infections "H Quentini"mentioning
confidence: 99%